Intellectual Capital And Knowledge Management: A Comparative Study In Malaysia - Chua , Chong Keow (2002)
This study compares non-service and service industries in Malaysia in terms of the use of Intellectual Capital(IC) and its effect on Performance (PER). It investigates as well the relationship between IC and Knowledge Managemen (KM). IC is the knowledge "stock" ( Stewart, 1997:111; Bontis, 1999:1) and KM is the knowledge "flow" (Bontis, 1999: 9). IC consists of Human Capital (HC) and Customer Capital (CC) which can only be shared by companies. Whereas, Structural capital (SC) is entirely owned by the companies. Good people may leave resulting in a "brain drain" (Chin, 2001). For the data collection, 164 Senior Malaysian managers from both non-Multimedia Super Corridor(MSC) and MSC enterprises were selected.